2011
DOI: 10.3136/fstr.17.523
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbonation with Heating on Germination of Bacillus subtilis Spores

Abstract: The effects of carbonation with heating (CH) on germination of Bacillus subtilis spores were investigated. Treatment conditions for CH and heat treatment alone were set to obtain an approximate 1 log reduction in viable count. Pre-treatment of spores with CH at 80℃ and 5 MPa for 30 min significantly decreased their heat resistance to a subsequent heating process at 90℃ for 30 min, as compared with pretreatment by heat alone at 90℃ for 30 min. Treatment with CH also decreased refractility and enhanced DAPI stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Some decrease in resistance is observed at the initial stage of germination, and then loss of refractility, decrease in optical density, and increase in permeability of fluorescent dyes are induced in the process of spore germination (Hachisuka, 1988). We previously reported that CH induced these phenomena in B. subtilis spores suspended in water (Noma et al, 2011). This raises the possibility that MC 10 facilitates the germination of B. subtilis spores by CH.…”
Section: Effect Of Ch In the Presence Of MC 10 On Germination Of Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Some decrease in resistance is observed at the initial stage of germination, and then loss of refractility, decrease in optical density, and increase in permeability of fluorescent dyes are induced in the process of spore germination (Hachisuka, 1988). We previously reported that CH induced these phenomena in B. subtilis spores suspended in water (Noma et al, 2011). This raises the possibility that MC 10 facilitates the germination of B. subtilis spores by CH.…”
Section: Effect Of Ch In the Presence Of MC 10 On Germination Of Bmentioning
confidence: 99%
“…A schematic diagram of the apparatus for CH is shown in a previous paper (Noma et al, 2011). A test tube containing 1 mL spore suspension was immersed in salad oil at 80℃ in a CO 2 -dissolving vessel.…”
Section: Carbonation With Heating (Ch) and Heat Treatment (Ht)mentioning
confidence: 99%
“…After standing for 30 min, the CO 2 gas in the vessel was released via a pressure-control valve. The equipment for carbonation is described in a previous paper (Noma et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that carbonation treatment has the potential to sterilize vegetative cells at a lower temperature than heat treatment (Rao et al, 2016). However, carbonation treatment has a poor inactivation effect on bacterial spores; treatment at 80℃, 5 MPa for 30 min yielded only a 1 log-order inactivation effect on Bacillus subtilis spores (Noma et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The authors described that carbonation might initiate spore germination due to lytic germination enzymes, which are known to be initiated by hydrostatic pressure; however, lytic enzymes could not contribute to carbonation-germination due to the low pH used during treatment. One explanation of the effect of CH on bacterial spores is that the protons generated during CH neutralize the negative charge on the cortex layer, inducing germination (Noma et al, 2011). Germinated spores might be more permeable to various substances, indicating the possibility that CH-induced germination could contribute to the combined effect of CH with FAEs.…”
Section: Discussionmentioning
confidence: 99%